2019
DOI: 10.1111/jth.14330
|View full text |Cite
|
Sign up to set email alerts
|

Chronic liver injury drives non‐traditional intrahepatic fibrin(ogen) crosslinking via tissue transglutaminase

Abstract: Introduction: Intravascular fibrin clots and extravascular fibrin deposits are often implicated in the progression of liver fibrosis. However, evidence supporting a pathological role of fibrin in hepatic fibrosis is indirect and based largely on studies using anticoagulant drugs that inhibit activation of the coagulation protease thrombin, which has other downstream targets that promote fibrosis. Therefore, the goal of this study was to determine the precise role of fibrin deposits in experimental hepatic fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 59 publications
(88 reference statements)
0
23
0
Order By: Relevance
“…53 Future studies should investigate differential activation of hepatic stellate cells by these 2 different PAR-1 agonists. Finally, there is also a need to better evaluate intrahepatic thrombin activity in the injured liver.Whereas numerous studies use intrahepatic fibrin(ogen) deposition as an index of hepatic thrombin activity, our recent studies indicate this may not be a reliable indicator of intrahepatic coagulation 14.…”
mentioning
confidence: 79%
See 2 more Smart Citations
“…53 Future studies should investigate differential activation of hepatic stellate cells by these 2 different PAR-1 agonists. Finally, there is also a need to better evaluate intrahepatic thrombin activity in the injured liver.Whereas numerous studies use intrahepatic fibrin(ogen) deposition as an index of hepatic thrombin activity, our recent studies indicate this may not be a reliable indicator of intrahepatic coagulation 14.…”
mentioning
confidence: 79%
“…Hepatic fibrosis was quantified using multiple complementary approaches as described previously. 14 For assessment of chronic liver injury, paraffin-embedded liver sections were stained with hematoxylin and eosin and examined by a board-certified veterinary pathologist (KJW) in a blinded fashion.…”
Section: Histopathology and Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, both molecules may be present as monomers or fibrillar polymers and the relative amount of each species could be quite heterogenous. Recent analyses on the contribution of fibrin(ogen) to liver injury have suggested that not only are deposits of fibrinogen, fibrin, and cross-linked fibrin present within injured zones but that each molecule exerts unique effects on cells in the microenvironment to influence distinct aspects of tissue injury, remodeling, and repair (18). It is possible that similar unique fibrin(ogen)-driven contributions could be made in AD.…”
mentioning
confidence: 99%
“…In this issue of the Journal of Thrombosis and Haemostasis , Poole et al . present data that made me wonder whether everything I have been taught in the 20 years in which I have studied thrombosis and hemostasis is wrong . In a mouse model of chronic liver injury, it was demonstrated that crosslinked fibrin(ogen) is deposited in a process that does not require fibrinogen‐to‐fibrin conversion or factor XIII.…”
mentioning
confidence: 99%